Metal paste for silicon nitride high-temperature co-fired ceramic and preparation method thereof
Patent Information
- Application Number
- CN202510521038.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]但是,氮化硅陶瓷的烧结温度较高,高温下会与钨发生反应,并且二者的热膨胀系数与烧结收缩也不匹配,容易出现分层、翘曲和金属层脱落等问题
(1)本发明通过加入少量的碳化硅作为无机粘结相,可以降低共烧陶瓷金属层的热膨胀系数,促进钨的烧结,提高其与陶瓷烧结收缩的匹配性;烧结过程中,碳化硅与钨在较低温度下发生反应生成的硅化钨与碳化钨,能够形成新的界面,降低烧结活化能,促进金属层致密;同时,这些产物相沿钨晶界偏析导致的晶粒细化,以及棒状硅化钨相的桥接作用,能够提高金属层强度,进而使其能够在后续高温烧结过程中,抵抗陶瓷层β-氮化硅晶粒的穿插引起的变形,维持平整;在此基础上,插入内部金属层的β-氮化硅晶粒也有利于提高界面结合强度,并促进陶瓷-金属层的同步收缩;上述协同作用最终能够有效地减少共烧陶瓷的脱层、翘曲等现象的发生,制得平整、方阻值较低的氮化硅高温共烧陶瓷;
Smart Images

Figure CN122977870A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature co-fired ceramics preparation technology, specifically relating to a metal slurry for silicon nitride high-temperature co-fired ceramics and its preparation method. Background Technology
[0002] High-temperature co-fired ceramics, due to their high sintering temperature, possess higher mechanical strength, thermal conductivity, and better chemical stability, while also offering advantages such as high wiring density. They hold broad application prospects in fields such as microwave devices and very large-scale integrated circuits, where the requirements for substrate thermal stability, strength, and hermeticity are more stringent. Currently, the main types of high-temperature co-fired ceramics are alumina and aluminum nitride. Alumina ceramics have poor thermal conductivity, while aluminum nitride ceramics suffer from low strength. In recent years, silicon nitride ceramics, researched and prepared both domestically and internationally, have shown continuously improved thermal conductivity, while their flexural strength and fracture toughness are more than twice that of the former two. Furthermore, silicon nitride ceramics exhibit excellent thermal shock resistance and corrosion resistance, enabling them to withstand harsh working environments with fluctuating power and rapid temperature changes, making them a preferred material for preparing novel high-temperature co-fired ceramics.
[0003] However, silicon nitride ceramics have a high sintering temperature, at which they react with tungsten. Furthermore, the coefficients of thermal expansion of the two materials do not match the sintering shrinkage, easily leading to problems such as delamination, warping, and metal layer detachment. Therefore, preparing a suitable metal paste is a prerequisite for obtaining smooth silicon nitride high-temperature co-fired ceramics. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a metal paste for silicon nitride high-temperature co-fired ceramics and its preparation method. By using a metal paste with a specific proportion of inorganic binder phase, the formation of a complete and continuous metal layer can be promoted, while improving the interfacial bonding strength and increasing the matching of sintering shrinkage, thereby obtaining a smooth and warp-free silicon nitride high-temperature co-fired ceramic.
[0005] In a first aspect, the present invention provides a metal slurry for silicon nitride high-temperature co-fired ceramics, wherein the chemical composition of the metal slurry for silicon nitride high-temperature co-fired ceramics includes: 14-29 wt% organic carrier, 70-85 wt% tungsten powder, and 0.1-2 wt% inorganic binder phase; wherein the inorganic binder phase includes silicon carbide.
[0006] Preferably, the organic carrier has the following chemical composition: 86-92 wt% solvent, 3-6 wt% thickener, and 5-8 wt% other additives.
[0007] Preferably, the solvent comprises at least two of α-terpineol, diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, and tributyl citrate; The thickener includes at least one of ethyl cellulose, polyvinyl butyral, and polyacrylic acid resin; The other adjuvants include at least two of sorbitan trioleate, trioleic acid glyceride, butyl benzyl phthalate, cetyl alcohol, and hydrogenated castor oil.
[0008] Preferably, the tungsten powder is spherical particles with a particle size range of 0.5 to 2 μm.
[0009] Secondly, the present invention provides a method for preparing the above-mentioned metal slurry for high-temperature co-fired silicon nitride ceramics, the preparation method comprising the following steps: (1) The solvent, thickener and other additives are heated and stirred according to the above ratio to obtain an organic carrier; (2) The tungsten powder and inorganic binder phase are mixed by coherent milling until the color is uniform to obtain a mixed powder; (3) The organic carrier and the mixed powder are heated and ball-milled to form a uniform paste, thereby obtaining the metal slurry for silicon nitride high-temperature co-fired ceramics.
[0010] Preferably, in step (1), the heating and stirring temperature is 60-90°C and the time is 2-4 hours.
[0011] Preferably, in step (2), the dry grinding and mixing is carried out in a plastic bottle for 3 to 6 hours and at a speed of 30 to 60 rpm.
[0012] Preferably, in step (3), the temperature of the heated ball milling mixture is 60-90°C, the rotation speed is 300-600 rpm, the ball milling time is 4-8 h, and the grinding medium is tungsten carbide balls.
[0013] Beneficial effects (1) By adding a small amount of silicon carbide as an inorganic binder phase, this invention can reduce the thermal expansion coefficient of the co-fired ceramic metal layer, promote the sintering of tungsten, and improve its matching with the sintering shrinkage of the ceramic. During the sintering process, the tungsten silicide and tungsten carbide generated by the reaction of silicon carbide and tungsten at a lower temperature can form a new interface, reduce the sintering activation energy, and promote the densification of the metal layer. At the same time, the grain refinement caused by the segregation of these product phases along the tungsten grain boundaries, as well as the bridging effect of the rod-shaped tungsten silicide phase, can improve the strength of the metal layer, thereby enabling it to resist the deformation caused by the penetration of β-silicon nitride grains in the ceramic layer during subsequent high-temperature sintering and maintain flatness. On this basis, the β-silicon nitride grains inserted into the internal metal layer are also conducive to improving the interface bonding strength and promoting the synchronous shrinkage of the ceramic-metal layer. The above synergistic effect can ultimately effectively reduce the occurrence of delamination, warping and other phenomena in co-fired ceramics, and obtain flat silicon nitride high-temperature co-fired ceramics with low sheet resistance. (2) The present invention makes the paste have good storage and screen printing characteristics by adjusting the proportion of organic carrier components; the appropriate viscosity and thixotropy can make the metal paste maintain a stable state when not in use, which is conducive to storage; while exhibiting sufficient fluidity during printing, ensuring that the paste can pass through the mesh and be evenly coated on the surface of the green ceramic tape; the viscosity recovers quickly after printing to prevent the paste from leaking and ensure the clarity of the printed pattern; the amount of thickener and other additives is small, which is conducive to the de-adhesion process. Attached Figure Description
[0014] Figure 1 This is a photograph of the silicon nitride high-temperature co-fired ceramic obtained in Example 1; Figure 2 , 3 This is a SEM image of the cross-section of the silicon nitride high-temperature co-fired ceramic obtained in Example 1. Detailed Implementation
[0015] The present invention will be further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.
[0016] First, this invention provides a metal paste for silicon nitride high-temperature co-fired ceramics. The chemical composition of this metal paste may include: 14–29 wt% organic carrier, 70–85 wt% tungsten powder, and 0.1–2 wt% inorganic binder phase. The contents of these three components can be matched according to the required thickness of the printed metal layer; the lower the organic carrier content, the thicker the printed metal layer. An excessively thick metal layer can easily cause problems such as delamination and deformation, while an excessively thin metal layer will result in decreased conductivity.
[0017] In some embodiments, the chemical composition of the organic carrier may include: 86-92 wt% solvent, 3-6 wt% thickener, and 5-8 wt% other additives. Excessive amounts of thickener and other poorly soluble organic substances such as additives are not recommended; otherwise, it will hinder the uniform mixing of the metal slurry during ball milling and may cause bubbling during debinding.
[0018] The solvent may include at least two of α-terpineol, diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, and tributyl citrate. α-Terpineol is a common solvent for preparing tungsten paste and is miscible with most reagents; tributyl citrate and diethylene glycol butyl ether acetate have high volatilization temperatures and good solubility with other solvents and reagents; ethylene glycol ethyl ether acetate can efficiently dissolve thickeners, preventing excessively high local viscosity of the paste, and also acts as a plasticizer. The mixed use of multiple solvents can meet the evaporation gradient requirements of the organic carrier and improve the solubility of each component.
[0019] The thickener may include at least one of ethyl cellulose, polyvinyl butyral, and polyacrylic acid resin.
[0020] The other additives may include at least two of sorbitan trioleate, trioleic acid glyceride, butyl benzyl phthalate, cetyl alcohol, and hydrogenated castor oil. The main function of these other additives is to provide thixotropy and leveling properties, and to ensure uniform dispersion of the powder in the organic carrier. Dispersibility and leveling properties primarily rely on surfactants, while thixotropy primarily relies on reagents that can gel in organic solvents through hydrogen bonding, forming a thixotropic network structure.
[0021] In some embodiments, the tungsten powder can be spherical particles with a particle size range of 0.5–2 μm. Too small a particle size will result in a thinner printed film, while a too wide particle size distribution will lead to an uneven film.
[0022] In some embodiments, the inorganic binder phase may include silicon carbide. By adding a small amount of silicon carbide as an inorganic binder phase, this invention can reduce the coefficient of thermal expansion of the co-fired ceramic metal layer, promote tungsten sintering, and improve its compatibility with ceramic sintering shrinkage. Simultaneously, it can generate a complete and continuous metal layer, improving interfacial bonding strength and increasing the compatibility with sintering shrinkage, which is beneficial for obtaining flat, warp-free high-temperature co-fired silicon nitride ceramics. During sintering, the product phase generated by the reaction of silicon carbide and tungsten at a lower temperature can form a new interface, reducing the sintering activation energy and promoting densification. Furthermore, the grain refinement caused by the segregation of the product phase along the tungsten grain boundaries, and the bridging effect of the rod-shaped tungsten silicide phase, can improve the strength of the metal layer, enabling it to resist deformation caused by the interpenetration of β-silicon nitride grains in the ceramic layer during subsequent high-temperature sintering, maintaining flatness. On this basis, the β-silicon nitride grains inserted into the internal metal layer also help improve interfacial bonding strength and promote synchronous shrinkage of the ceramic-metal layer.
[0023] It should also be noted that this invention achieves excellent storage and screen printing properties in the paste through the adjustment of the organic carrier component ratio. Suitable viscosity and thixotropy allow the metal paste to remain stable when not in use, facilitating storage. During printing, it exhibits sufficient fluidity, ensuring the paste can pass through the mesh and be evenly coated onto the surface of the green ceramic tape; after printing, the viscosity recovers rapidly, preventing paste leakage and ensuring the clarity of the printed pattern. The use of thickeners and other additives is minimal, which is beneficial for the debinding process.
[0024] In some embodiments, the thixotropic index (the difference between viscosity at low and high shear rates / viscosity at low shear rate) of the metal slurry for silicon nitride high-temperature co-fired ceramics can be 87-99%, and the thixotropic time (the time required for the viscosity to recover to 50% after the high shear rate is converted to the low shear rate) can be 1.5-5.0 s.
[0025] The following is an exemplary description of a method for preparing a metal slurry for high-temperature co-fired silicon nitride ceramics provided by the present invention. The preparation method may include the following steps: (1) The solvent, thickener and other additives are heated and stirred according to the above ratio to obtain an organic carrier; (2) The tungsten powder and inorganic binder phase are mixed by coherent milling until the color is uniform to obtain a mixed powder; (3) The organic carrier and the mixed powder are heated and ball-milled to form a uniform paste, thereby obtaining the metal slurry for silicon nitride high-temperature co-fired ceramics.
[0026] In some embodiments, in step (1), the heating and stirring temperature can be 60–90°C, and the time can be 2–4 hours. The thickener and some other additives, which are poorly soluble, can be added in multiple batches, allowing them to dissolve completely before further addition to improve dissolution efficiency. If the temperature is too low, the poorly soluble components will dissolve slowly, resulting in an uneven organic carrier; if the temperature is too high, a large amount of low-boiling-point solvent will evaporate, making the content of the organic carrier components uncontrollable.
[0027] In some embodiments, in step (2), the dry grinding and mixing can be carried out in a plastic bottle for 3 to 6 hours at a speed of 30 to 60 rpm.
[0028] In some embodiments, in step (3), the temperature of the heated ball milling mixture can be 60-90°C, the rotation speed can be 300-600 rpm, the ball milling time can be 4-8 h, and the grinding medium can be tungsten steel balls.
[0029] The metal slurry provided by this invention, after being co-fired with silicon nitride ceramic at high temperature, allows for the testing of the sheet resistance of the material using the four-probe method, and the microstructure of the surface and cross-section of the metal layer can be characterized.
[0030] In some embodiments, the sheet resistance of the ceramic material after high-temperature co-firing of the slurry and silicon nitride can be 5 to 30 mΩ / □.
[0031] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the range based on the description herein, and are not intended to be limited to the specific values in the examples below. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0032] Example 1
[0033] The method for preparing the metal slurry for high-temperature co-fired silicon nitride ceramics provided in this embodiment includes the following steps: (1) Place 54g of α-terpineol, 27g of diethylene glycol butyl ether acetate, 9g of ethylene glycol ethyl ether acetate and 3g of sorbitan trioleate into a beaker, stir evenly and heat to 80°C. Add 4.5g of ethyl cellulose and 2.5g of hydrogenated castor oil in three portions. After each addition, heat and stir for 1 hour until completely dissolved to obtain a clear liquid organic carrier. Heat to 80°C for later use. (2) 99g of 0.5μm tungsten powder and 1g of silicon carbide were pre-mixed by dry grinding in a plastic bottle for 6 hours at a speed of 42 rpm until the powder color was uniform. (3) Place 100g of the mixed powder and 35g of the heated organic carrier into a ball mill jar and ball mill for 4 hours at a speed of 380 rpm. The grinding media is tungsten steel balls. After the metal slurry cools down, continue to heat it to 80°C and continue ball milling for 2 hours. Repeat this step until the slurry is uniformly pasty at room temperature to obtain the metal slurry for silicon nitride high-temperature co-fired ceramics (25.9wt% organic carrier, 73.4wt% tungsten powder, 0.7wt% inorganic binder phase).
[0034] After co-firing the silicon nitride high-temperature co-fired ceramic with the metal slurry, the sample was flat, the surface metal layer was intact and without cracks, and the sheet resistance was 10.0 mΩ / □.
[0035] Figure 1 The image shows a physical photograph of the silicon nitride co-fired ceramic obtained in Example 1. As can be seen from the image, the sample is flat and free of warping, with a complete and clear surface metal pattern and straight, undeformed internal metal lines.
[0036] Figure 2 , 3 The image shows a SEM image of the cross-section of the silicon nitride co-fired ceramic obtained in Example 1. As can be seen from the image, the sintered metal layer is of uniform thickness, flat and continuous, without delamination, and exhibits good interfacial bonding.
[0037] Example 2
[0038] The preparation method of the metal slurry for silicon nitride high-temperature co-fired ceramics provided in this embodiment is the same as in Example 1, with the main difference being: In step (2), 99.5g of tungsten powder and 0.5g of silicon carbide are used; The obtained high-temperature co-fired silicon nitride ceramic metal slurry contains 25.9 wt% organic carrier, 73.7 wt% tungsten powder, and 0.4 wt% inorganic binder phase.
[0039] After co-firing the aforementioned high-temperature co-fired silicon nitride ceramic metal slurry with silicon nitride ceramic, the sample was flat, the surface metal layer was intact without macroscopic cracks, and the sheet resistance was 17.1 mΩ / □.
[0040] Example 3
[0041] The preparation method of the metal slurry for silicon nitride high-temperature co-fired ceramics provided in this embodiment is the same as in Example 1, with the main difference being: In step (2), 98.5g of tungsten powder and 1.5g of silicon carbide are used; The obtained high-temperature co-fired silicon nitride ceramic metal slurry contains 25.9 wt% organic carrier, 73.0 wt% tungsten powder, and 1.1 wt% inorganic binder phase.
[0042] After co-firing the silicon nitride high-temperature co-fired ceramic with the metal slurry, the sample was flat, the surface metal layer was intact and without cracks, and the sheet resistance was 13.5mΩ / □.
[0043] Comparative Example 1
[0044] The preparation method of the metal paste provided in this comparative example is the same as that in Example 1, with the main difference being: In step (2), no silicon carbide was added; The resulting metal slurry contained 25.9 wt% organic carrier and 74.1 wt% tungsten powder.
[0045] After co-firing the above metal slurry with silicon nitride ceramic, the sample was partially warped, and there were obvious cracks in the surface metal layer, making the sheet resistance unmeasurable.
[0046] Comparative Example 2
[0047] The preparation method of the metal paste provided in this comparative example is the same as that in Example 1, with the main difference being: In step (2), 99.9g of tungsten powder and 0.1g of silicon carbide are used; The resulting metal slurry contained 25.93 wt% organic carrier, 74.00 wt% tungsten powder, and 0.07 wt% inorganic binder phase.
[0048] After co-firing the above metal paste with silicon nitride ceramic, the sample edges warped, a small number of microcracks appeared in the surface metal layer, and the sheet resistance was 252.7mΩ / □.
[0049] Comparative Example 3
[0050] The preparation method of the metal paste provided in this comparative example is the same as that in Example 1, with the main difference being: In step (2), 95.0g of tungsten powder and 5g of silicon carbide are used; The resulting metal slurry contained 25.9 wt% organic carrier, 70.4 wt% tungsten powder, and 3.7 wt% inorganic binder phase.
[0051] After co-firing the above metal paste with silicon nitride ceramic, the sample bent slightly downwards. The surface metal layer was intact and without cracks, but the metallic luster was significantly reduced, and the sheet resistance was 43.2 mΩ / □.
[0052] As can be seen from the above examples and comparative examples, the addition of a small amount of silicon compound as an inorganic binder phase in this invention can generate a complete and continuous metal layer, while improving the interfacial bonding strength and increasing the matching of sintering shrinkage, which is beneficial to obtaining flat and warp-free silicon nitride high-temperature co-fired ceramics.
[0053] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A metal paste for high-temperature co-fired silicon nitride ceramics, characterized in that, The chemical composition of the metal slurry for high-temperature co-fired silicon nitride ceramics includes: 14-29 wt% organic carrier, 70-85 wt% tungsten powder, and 0.1-2 wt% inorganic binder phase; the inorganic binder phase includes silicon carbide.
2. The metal slurry for high-temperature co-fired silicon nitride ceramics according to claim 1, characterized in that, The organic carrier has the following chemical composition: 86-92 wt% solvent, 3-6 wt% thickener, and 5-8 wt% other additives.
3. The metal slurry for high-temperature co-fired silicon nitride ceramics according to claim 1 or 2, characterized in that, The solvent includes at least two of α-terpineol, diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, and tributyl citrate; The thickener includes at least one of ethyl cellulose, polyvinyl butyral, and polyacrylic acid resin; The other adjuvants include at least two of sorbitan trioleate, trioleic acid glyceride, butyl benzyl phthalate, cetyl alcohol, and hydrogenated castor oil.
4. The metal paste for silicon nitride high-temperature co-fired ceramics according to any one of claims 1-3, characterized in that, The tungsten powder is in the form of spherical particles with a particle size range of 0.5–2 μm.
5. A method for preparing a metal slurry for silicon nitride high-temperature co-fired ceramics according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: (1) The solvent, thickener and other additives are heated and stirred according to the above ratio to obtain an organic carrier; (2) The tungsten powder and inorganic binder phase are mixed by coherent milling until the color is uniform to obtain a mixed powder; (3) The organic carrier and the mixed powder are heated and ball-milled to form a uniform paste, thereby obtaining the metal slurry for silicon nitride high-temperature co-fired ceramics.
6. The preparation method according to claim 5, characterized in that, In step (1), the heating and stirring temperature is 60-90℃ and the time is 2-4h.
7. The preparation method according to claim 5 or 6, characterized in that, In step (2), the dry grinding and mixing is carried out in a plastic bottle for 3 to 6 hours and at a speed of 30 to 60 rpm.
8. The preparation method according to any one of claims 5-7, characterized in that, In step (3), the temperature of the heated ball milling mixture is 60-90℃, the rotation speed is 300-600rpm, the ball milling time is 4-8h, and the grinding medium is tungsten steel balls.
